Numerical Investigation and Wind Tunnel Validation on Near-Wake Vortical Structures of Wind Turbine Blades (Advances in Applied Mathematics and Mechanics, 2018)
Computational fluid dynamics (CFD) has been used by numerous researchersfor the simulation of flows around wind turbines. Since the 2000s, the experimentsof NREL phase VI blades for blind comparison have been a de-facto standardfor numerical software on the prediction of full scale horizontal axis wind turbines(HAWT) performance. However, the characteristics of vortex structures in the wake,whether for modeling the wake or for understanding the aerodynamic mechanismsinside, are still not thoroughly investigated. In the present study, the flow around NRELphase VI blades was numerically simulated, and the results of the wake field werecompared with the experimental ones of a one-to-eight scaled model in a low-speedwind tunnel. A good agreement between simulation and experimental results wasachieved for the evaluation of overall performances. The simulation captured the completeformation procedure of tip vortex structure from the blade. Quantitative analysisshowed the streamwise translation movement of vortex cores. Both the initial formationand the damping of vorticity in near wake field were predicted. These numericalresults showed good agreements with the measurements. Moreover, wind tunnel walleffects were also investigated on these vortex structures, and it revealed further radialexpansion of the helical vortical structures in comparison with the free-stream case.